Removal method of surface protective coating film of object to be coated
Patent Information
- Application Number
- JP2024150208
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-14
AI Technical Summary
【0011】 本発明の塗膜除去方法によれば、容易に表面保護塗膜を除去することが可能な塗膜除去方法を提供することができる。
Smart Images

Figure 2025036379000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for removing a protective coating film formed on the surface of an object to be coated. [Background technology]
[0002] Conventionally, resin wax has been applied to the floors of buildings such as office buildings, commercial facilities, and public facilities to improve their scratch resistance and gloss. However, floors coated with resin wax are prone to numerous scratches and stains due to walking and transporting materials on a cart, and the gloss also decreases in a relatively short period of time, so there is a problem that maintenance is required several times a year. For this reason, a floor coating agent that is resistant to scratches and gloss loss is desired.
[0003] For example, Patent Document 1 discloses an active energy ray-curable resin composition for flooring, which is characterized by containing a bifunctional urethane (meth)acrylate resin (A), an epoxy (meth)acrylate resin (B), and a polyolefin wax (C).
[0004] Furthermore, in Patent Document 2, the applicant proposed a coating composition for protecting floor surfaces, which contains (A) an epoxy silane oligomer having an epoxy group and a siloxane bond and a weight average molecular weight of 500 to 20,000, (B) colloidal silica having an average primary particle size in the range of 1 to 100 nm, and (C) a curing catalyst.
[0005] On the other hand, methods for removing coating films have also been proposed to return floors protected by these floor coating agents to their original state. For example, Patent Document 3 describes a hard coating film remover that is made of a type of inorganic powder agent or a mixture of these, has a Vickers hardness (HV) of 3 to 20 (GPa), a particle size of 30 μm to 300 μm, and a specific gravity of 0.1 or more. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-141104 A [Patent Document 2] WO2018 / 151271 publication [Patent Document 3] JP 2023-20782 A Summary of the Invention [Problem to be solved by the invention]
[0007] The physical scraping method using an inorganic powder as described in Patent Document 3 may not be able to fully remove the coating film depending on the type of flooring material. For example, when removing a high-hardness coating film applied to a material with fine irregularities on the surface such as a polyvinyl chloride sheet, there is a problem that the coating film that has entered the recesses cannot be completely removed without damaging the flooring material.
[0008] An object of the present invention is to provide a coating removal method that can easily remove a surface protective coating. [Means for solving the problem]
[0009] The present inventors have conducted extensive research into the above-mentioned problems, and as a result have found that even a highly hard surface protective coating formed on a substrate having fine recesses can be easily removed by grinding off a portion of the outermost surface of the surface protective coating, applying an alkaline stripping agent, and then grinding the surface protective coating again.
[0010] That is, the present invention provides: Item 1 A substrate having a surface protective coating film with a glassy hard coat as a top coat is provided with A step (I) of grinding the glassy hard coat using an abrasive (A) containing abrasive grains; A step (II) of applying an alkaline stripping agent (B) to the glassy hard coat having the grinding marks formed in the step (I) to allow the stripping agent (B) to penetrate into the glassy hard coat; A step (III) of grinding the vitreous hard coat treated with alkali in the step (II) with an abrasive (C) containing abrasive grains to remove the surface protective coating film and expose the substrate; A method for removing a surface protective coating film from an object to be coated. Section 2 Item 2. The method for removing the coating liquid according to item 1, wherein the surface of the coating object is flat or uneven. Section 3 Item 3. The method for removing the hard coat according to item 1 or 2, wherein the hard coat comprises a silica skeleton derived from three-dimensional siloxane bonds as a main component. Section 4 4. The method for removing the hard coat according to any one of items 1 to 3, wherein the hard coat is formed by applying a coating agent containing a hydrolyzable silane and / or a condensate thereof, and colloidal silica. Section 5 5. The removal method according to any one of items 1 to 4, wherein the surface protective coating is a multi-layer coating in which the top coat is the vitreous hard coat and the primer coat is a polyurethane coating. Section 6 6. The removing method according to any one of items 1 to 5, wherein the abrasive (A) is a diamond pad having a grain size of #40 to #240. Section 7 7. The removing method according to any one of items 1 to 6, wherein the abrasive (A) is disk-shaped and is attached to a rotary electric polisher. Section 8 8. The method for removing according to any one of items 1 to 7, further comprising the step of covering the surface protective coating with a sheet material after step (II) and before step (III). Section 9 9. The removing method according to any one of items 1 to 8, wherein the abrasive (C) is a diamond pad having a grain size of #40 to #1000. Item 10 10. The removing method according to any one of Items 1 to 9, wherein the abrasive (C) is disk-shaped and attached to a rotary electric polisher. Regarding. Effect of the Invention
[0011] According to the coating removal method of the present invention, it is possible to provide a coating removal method that can easily remove a surface protective coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The coating removal method of the present invention is aimed at a coated article having a surface protective coating with a glassy hard coat as the top coat.
[0013] Object to be coated: In the present invention, examples of the substrate to be coated before a surface protective coating is provided (hereinafter, sometimes referred to as "substrate") include planar building materials such as flooring and wall materials, planar furniture components such as tables, washstands, and counters, etc. Examples of materials for the substrate include resin-based materials, wood-based materials, ceramic-based materials, stone materials, concrete-based materials, etc. An example of a resin-based material is vinyl chloride. Substrates made of this material are classified into tiles and sheets. Generally, tiles are hard, while sheets are flexible. Specific examples of substrates made of vinyl chloride material include vinyl chloride tiles such as composition vinyl floor tiles and homogeneous vinyl floor tiles; vinyl chloride sheets such as foam floor sheets such as cushion flooring, woven fabric laminated vinyl floor sheets, and nonwoven fabric laminated vinyl floor sheets.
[0014] Examples of wood-based materials include natural wood and plywood, examples of ceramic-based materials include porcelain and ceramics, examples of stone materials include marble and granite, and examples of concrete-based materials include mortar. The surface of the substrate may be flat or uneven, such as embossed, debossed, or textured with fine concave and / or convex shapes, such as a woven fabric or wood grain pattern. The method of the present invention is particularly effective when the substrate is a flexible sheet having a concave pattern, in that it can easily remove even a high-hardness surface protective coating formed on a substrate having a fine concave pattern.
[0015] Glassy hard coat: The glassy hard coat is preferably a high-hardness coating film containing, as a main component, a silica skeleton derived from highly crosslinked three-dimensional siloxane bonds, from the viewpoint of being able to strongly protect the substrate and being easily removable with a release agent (B) and an abrasive (C). In this specification, the term "main component" refers to a component that is contained in an amount of preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more and 100% by mass or less as solid content in the total constituent components. For example, the Martens hardness is 100 to 300 N / mm 2 , especially 120~300N / mm 2 In this specification, the Martens hardness can be measured using an ultra-microhardness tester (e.g., Fisherscope HM-2000 (product name) manufactured by Fisher Instruments Co., Ltd.) under conditions of 23°C and 50% relative humidity and a load of 20 mN / 25 seconds using a Vickers indenter.
[0016] The glassy hard coat can be, for example, formed by applying a coating agent containing a hydrolyzable silane and / or a condensate thereof and colloidal silica.
[0017] Hydrolyzable silanes and / or their condensates: Examples of hydrolyzable silanes include alkoxysilyl group-containing compounds, and specific examples of hydrolyzable silanes and / or condensates thereof include alkylalkoxysilanes, alkyl silicates, epoxy silane oligomers, silane coupling agents, etc. From the viewpoint of coating film removability, it is particularly preferable that the hydrolyzable silanes and / or condensates thereof contain alkylalkoxysilanes, epoxy silane oligomers, and silane coupling agents.
[0018] Alkylalkoxysilane: Examples of the alkylalkoxysilane include trifunctional alkylalkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and p-styryltrimethoxysilane; Difunctional alkylalkoxysilanes such as dimethyldimethoxysilane, dimethyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, methylethyldimethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, methylpropyldimethoxysilane, and methylpropyldiethoxysilane; Monofunctional alkylalkoxysilanes such as trimethylmethoxysilane, trimethylethoxysilane, trimethylisopropylpropoxysilane, dimethylisobutylmethoxysilane; and combinations thereof. The content of the alkylalkoxysilane in the glassy hard coat is, for example, 1 to 40% by mass.
[0019] In the present invention, when the masses of the vitreous hard coat and the primer coat described below are not clear, the solid contents of the coating agent for forming the vitreous hard coat and the coating agent for forming the primer coat film can be regarded as the masses of the vitreous hard coat and the primer coat, respectively.
[0020] In this specification, the solid content means the residue remaining after removing volatile components such as water and non-aqueous solvents from a sample, and can be calculated by multiplying the mass of the sample by the solid content concentration. The solid content concentration can be determined by drying about 3 grams of a sample at 105°C for 3 hours and dividing the mass of the resulting residue by the mass before drying.
[0021] Alkyl silicate: The alkyl silicates include tetraalkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraphenoxysilane, and combinations thereof. The content of the alkyl silicate in the vitreous hard coat is, for example, within the range of 1 to 20 mass %.
[0022] Epoxy silane oligomer: The epoxy silane oligomer is a compound having an alkoxysilyl group, an epoxy group, and a siloxane bond in the molecule, and examples thereof include a hydrolysis condensation product of an epoxy group-containing alkoxysilane, and / or a hydrolysis condensation product of the epoxy group-containing alkoxysilane compound and an alkoxysilane having no epoxy group.
[0023] Examples of the epoxy group-containing alkoxysilane include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)methyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)methyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)methyldimethoxysilane. Examples of the alkoxysilane that does not have an epoxy group include the compounds exemplified as alkylalkoxysilanes and alkylsilicates. The weight average molecular weight of the epoxy silane oligomer is, for example, within a range of 500 to 20,000, particularly within a range of 800 to 10,000. The epoxy equivalent of the epoxy silane oligomer is, for example, within a range of 150 to 1,000 (g / eq), particularly within a range of 200 to 800 (g / eq).
[0024] In this specification, the weight average molecular weight is a value obtained by converting the retention time (retention volume) measured using a gel permeation chromatograph (GPC) into the molecular weight of polystyrene using the retention time (retention volume) of a standard polystyrene with a known molecular weight measured under the same conditions. Specifically, the gel permeation chromatograph is equipped with "HLC-8120GPC" (trade name, manufactured by Tosoh Corporation), and four columns, "TSKgel G4000HXL", "TSKgel G3000HXL", "TSKgel G2500HXL" and "TSKgel G2000HXL" (trade names, all manufactured by Tosoh Corporation), and a differential refractometer is used as a detector, and the measurement can be performed under the following conditions: mobile phase: tetrahydrofuran, measurement temperature: 40°C, flow rate: 1 mL / min. The epoxy equivalent is the number of grams of a resin containing 1 gram equivalent of epoxy groups measured by a method in accordance with JIS K7236. The content of the epoxy silane oligomer in the glassy hard coat is, for example, within the range of 20 to 80 mass %.
[0025] Silane coupling agent: Examples of the silane coupling agent include glycidoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 3-glycidoxypropylmethyldiethoxysilane; epoxy group-containing silane coupling agents such as (3,4-epoxycyclohexyl)methyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)methyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)methyldimethoxysilane; 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-2(aminoethyl)3-aminopropyltrimethoxysilane; Examples of the silane coupling agents include amino group-containing silane coupling agents such as pyrtrimethoxysilane and N-2(aminoethyl)3-aminopropylmethyldimethoxysilane; ureido group-containing silane coupling agents such as 3-ureidopropyltrialkoxysilane; mercapto group-containing silane coupling agents such as 3-mercaptopropyltrimethoxysilane; vinyl group-containing silane coupling agents such as vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltris(methoxyethoxy)silane; (meth)acryloyl group-containing silane coupling agents such as 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, and 3-(meth)acryloyloxypropyldimethoxymethylsilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.
[0026] The content of the silane coupling agent in the glassy hard coat is, for example, within the range of 1 to 70% by mass.
[0027] Colloidal Silica: Colloidal silica is a dispersion of ultrafine silica particles in a dispersion medium. Examples of the dispersion medium include water; alcohol-based solvents such as methanol, ethanol, isopropanol, n-propanol, isobutanol, and n-butanol; polyhydric alcohol-based solvents such as ethylene glycol; polyhydric alcohol derivatives such as ethylene glycol monoethyl ether and ethylene glycol monobutyl ether; ketone-based solvents such as methyl ethyl ketone, methyl isobutyl ketone, and diacetone alcohol; and monomers such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and tetrahydrofurfuryl acrylate. The average particle size of the colloidal silica is, for example, within a range of 1 to 100 nm, particularly within a range of 8 to 50 nm. In this specification, the average particle size of colloidal silica refers to the average particle size calculated by the nitrogen adsorption method (BET method), unless otherwise specified. The content of the colloidal silica in the vitreous hard coat is, for example, within a range of 20 to 80 mass % in terms of solid content.
[0028] The coating agent for forming a glassy hard coat may further contain additives such as a curing catalyst, water, an organic solvent, a coloring pigment, an extender pigment, a matting agent, an aggregate, a resin particle, a surface conditioner, a viscosity adjuster, an antifoaming agent, an antibacterial agent, an antifungal agent, a flame retardant, an antifogging agent, a plasticizer, a slip agent, a dehydrating agent, an ultraviolet absorbing agent, a light stabilizer, metal oxide fine particles, a metal powder, an antioxidant, a surfactant, a film-forming assistant, a thickener, an antistatic agent, a water repellency imparting agent, and fibers.
[0029] Of these, the curing catalyst is not particularly limited as long as it can promote curing by hydrolysis and condensation of a compound having an alkoxysilyl group, and examples thereof include phosphoric acid, orthophosphoric acid, metaphosphoric acid, pyrophosphoric acid, phosphorous acid, polyphosphoric acid, phosphonic acid, methanephosphonic acid, benzenephosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, phosphinic acid; alkali metal salts or ammonium salts of these phosphoric acid compounds; Inorganic acids such as hydrogen fluoride, hydrochloric acid, nitric acid, and sulfuric acid; Organic acids such as formic acid, acetic acid, propionic acid, oxalic acid, citric acid, maleic acid, benzoic acid, malonic acid, glutaric acid, and toluenesulfonic acid; Organoaluminum compounds such as aluminum trimethoxide, tris(acetylacetonate)aluminum, aluminum tri-n-butoxide, aluminum tris(acetylacetone), aluminum tris(ethyl acetoacetate), aluminum diisopropoxy(ethyl acetoacetate), and aluminum acetylacetonate; Organotitanium compounds such as titanium tetrakis(ethylene glycol monomethyl ether), titanium tetrakis(ethylene glycol monoethyl ether), titanium tetrakis(ethylene glycol monobutyl ether), and tetra-n-butyl titanate; Organic zirconium compounds such as zirconium tetrakis(ethylene glycol monomethyl ether), zirconium tetrakis(ethylene glycol monoethyl ether), zirconium tetrakis(ethylene glycol monobutyl ether), zirconium normal propylate, zirconium normal butylate, and zirconium tetrakis(acetylacetonate); organic zinc compounds such as zinc naphthenate; organic cobalt compounds such as cobalt octylate and cobalt naphthenate; boric acid, trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, triphenyl borate, tri(4-chlorophenyl) borate, and trihexafluoroborate. Examples of the curing catalyst include boric acid compounds such as boric acid esters such as fluoroisopropyl, alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, cesium hydroxide, and the like, ammonium hydroxide salts such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, and the like, ammonium fluoride salts such as tetrabutylammonium fluoride, and the like, amines such as diethylamine and triethylamine, ethanolamines such as monoethanolamine, triethanolamine, N-methyldiethanolamine, and the like, strong base tertiary amine compounds such as DBU, and combinations thereof. The above curing catalysts may be used alone or in combination of two or more kinds. The content of the curing catalyst in the glassy hard coat is, for example, within the range of 0.1 to 30% by mass.
[0030] Primer Coat: The surface protective coating may be one in which another primer coating is provided as an underlayer, provided that the topcoat is the glassy hard coating. The primer coating may be either an organic resin coating or an inorganic coating. Also, glassy hard coatings in which the blending ratio of each raw material contained in the glassy hard coating is different are included in the primer coating. In particular, when the primer coating is a polyurethane coating, it is highly effective in protecting the coated object together with the topcoat under normal conditions, and when removing the polyurethane coating, it is easy to remove even the coating that has entered the recessed portion, which is preferable.
[0031] The polyurethane coating is a flexible coating containing, as a main component, a polyurethane skeleton derived from urethane bonds. The Martens hardness is lower than that of the glassy hard coat, for example, 30 N / mm 2 More than 300N / m 2 Less than 50N / mm 2 More than 250N / mm 2 The polyurethane coating film is formed by applying a coating containing a base agent including a hydroxyl group-containing acrylic resin and a curing agent including a polyisocyanate compound.
[0032] Hydroxyl-containing acrylic resin: The hydroxyl group-containing acrylic resin is a component that forms a polyurethane crosslinked coating film that can serve as a primer coat together with a polyisocyanate compound described below. The hydroxyl-containing acrylic resin is usually a copolymer of a hydroxyl-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer.
[0033] Examples of hydroxyl group-containing polymerizable unsaturated monomers include monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified products of the monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms; and allyl alcohol.
[0034] Examples of other polymerizable unsaturated monomers copolymerizable with the hydroxyl group-containing polymerizable unsaturated monomer include alkyl or cycloalkyl (meth)acrylates such as methyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, tert-butyl (meth)acrylate, and cyclohexyl (meth)acrylate; polymerizable unsaturated monomers having an isobornyl group; polymerizable unsaturated monomers having an adamantyl group; vinyl aromatic compounds; polymerizable unsaturated monomers having an alkoxysilyl group; perfluoroalkyl (meth)acrylates; polymerizable unsaturated monomers having a fluorinated alkyl group; polymerizable unsaturated monomers having a photopolymerizable functional group such as a maleimide group; vinyl compounds; carboxylic acids such as (meth)acrylic acid, maleic acid, crotonic acid, fumaric acid, and itaconic acid, β-carboxyethyl (meth)acrylate, and dicarboxylic acid monoesters, and other carboxyl group-containing polymerizable unsaturated monomers; nitrogen-containing polymerizable unsaturated monomers; and polymerizable unsaturated monomers having two or more polymerizable unsaturated groups in one molecule. Monomers; epoxy group-containing polymerizable unsaturated monomers such as glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, and allyl glycidyl ether; (meth)acrylates having a polyoxyethylene chain whose molecular terminal is an alkoxy group; polymerizable unsaturated monomers having a sulfonic acid group; polymerizable unsaturated monomers having a phosphoric acid group; polymerizable unsaturated monomers having an ultraviolet absorbing functional group; ultraviolet stable polymerizable unsaturated monomers; polymerizable unsaturated monomer compounds having a carbonyl group such as acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formyl styrene, and vinyl alkyl ketones having 4 to 7 carbon atoms (e.g., vinyl methyl ketone, vinyl ethyl ketone, and vinyl butyl ketone), and combinations thereof.
[0035] Polyisocyanate compounds: The polyisocyanate is a compound having two or more free isocyanate groups in one molecule, and examples thereof include aliphatic diisocyanates such as tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; alicyclic diisocyanates such as 4,4'-methylenebis(cyclohexyl isocyanate) and isophorone diisocyanate; aromatic diisocyanates such as xylylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, and polyphenylmethane diisocyanate (hereinafter referred to as polymeric MDI); and derivative compounds such as isocyanurates and biuret forms of these. Also included are polyisocyanate compounds for aqueous coating materials, such as hydrophilized polyisocyanate compounds obtained by introducing hydrophilic groups such as polyether groups, carboxyl groups, sulfonic acid groups, phosphoric acid groups, or betaine structure-containing groups into the polyisocyanate compounds, and water-dispersible polyisocyanate compounds in which the polyisocyanate compounds can be made to be in a dispersed state in water using a surfactant.
[0036] The coating agent for forming the polyurethane coating film may contain, in addition to the above-mentioned components, additives such as water, an organic solvent, a curing catalyst, a resin other than a hydroxyl group-containing acrylic resin (e.g., a polyurethane resin), colloidal silica, a surface conditioner, an extender pigment, a coloring pigment, glass beads, resin particles, a dispersion stabilizer, a viscosity adjuster, an ultraviolet absorber, a light stabilizer, a film-forming auxiliary, a preservative, an antifoaming agent, a neutralizing agent, a silane coupling agent, a plasticizer, an antifreeze agent, a pH adjuster, and a flame retardant.
[0037] Process (I): In the present invention, step (I) is a step of grinding the vitreous hard coat with an abrasive (A) containing abrasive grains. The grinding process using abrasive (A) creates grinding marks on the surface of the glassy hard coat formed on the substrate. The grinding process is carried out by spraying water as necessary and pressing the abrasive (A) against the surface while moving it.
[0038] The abrasive (A) may be a powdered abrasive grain or a sheet-like abrasive grain attached to the surface of paper or cloth. The abrasive grain is a powder made of relatively high hardness particles. It may be an inorganic compound such as a metal compound or ceramic, or an abrasive grain powder made of an organic compound such as crushed plastic particles or cellulose. In the present invention, the abrasive grain is preferably an inorganic compound. The inorganic compound may be a natural or synthetic compound, and specifically includes diamond, alumina, silicon carbide, silicon nitride, boron carbide, boron nitride, diatomaceous earth, silica sand, silica, zirconia, iron oxide, chromium (III) oxide, and cerium (IV) oxide. From the viewpoint of exerting abrasive function or coating removal ability, diamond is particularly preferable.
[0039] The grain size of the abrasive (A) is preferably #40 to #240. By having the grain size within this range, cutting marks of appropriate depth and density can be generated in the depth direction and planar direction of the surface protective coating film, and the penetration of the subsequent alkaline stripping agent (B) is increased, thereby providing excellent coating removal properties. A diamond pad with a grain size of #40 to #240 is a preferred example of the abrasive (A).
[0040] In this specification, the grain size shall be the value given in the catalogue of the abrasive, and if it is not clear, it shall be determined in accordance with JIS R 6010: 2000. In addition, in this specification, "#" and "P" representing the grain size are synonymous.
[0041] The grinding operation may be performed manually or automatically. The rubbing direction is not particularly regular, but examples include a linear reciprocating motion in a horizontal direction relative to the surface protective coating, a rotational motion in which the rotation direction is horizontal to the surface protective coating (the rotation axis is perpendicular to the surface protective coating), a rotational motion in which the rotation direction is perpendicular to the surface protective coating (the rotation axis is horizontal to the surface protective coating), and combinations thereof. From the viewpoint of suppressing damage to the coated object and removing the protective coating that has entered the recesses, a polishing device that performs a rotational motion in which the rotation direction is horizontal to the surface protective coating is more preferable. In addition, the grinding operation may be performed once or multiple times at the same location.
[0042] As the polishing device, for example, commercially available devices such as an orbital sander, delta sander, random sander, disc grinder, belt sander, straight grinder, electric polisher, etc. can be used.
[0043] In the present invention, from the viewpoint of coating film removability, it is preferable that the abrasive (A) is disk-shaped and is attached to a rotary electric polisher. An electric polisher is, for example, a machine equipped with a rotating base at the bottom, on which a brush, a scrubbing brush, an abrasive, etc. is attached and rotated to wash, wax, or polish a coated object, and is generally used by building maintenance companies and cleaning companies.
[0044] Thus, the abrasive (A) forms a grinding mark on the glassy hard coat. The grinding mark does not necessarily have to be formed over the entire surface area of the glassy hard coat. Even if the grinding mark is formed partially, the subsequent step (II) of penetrating the alkaline stripping agent (B) is performed, so that the coating film can be sufficiently removed. When the grinding mark is formed partially, the area ratio of the part without any grinding mark (part untreated with the abrasive (A)) is, for example, 30% or less.
[0045] Process (II): In the method of the present invention, an alkaline stripping agent (B) is applied to the glassy hard coat having the grinding marks formed in the step (I). A stripping agent is a chemical used to strip a coating film, and dichloromethane stripping agents, non-dichloromethane stripping agents, alkaline stripping agents, neutral stripping agents, acidic stripping agents, etc. are commercially available. In the present invention, an alkaline stripping agent is used. By carrying out the step (I) and applying the alkaline stripping agent (B) to the grinding marks and allowing it to penetrate, even a strongly crosslinked high-hardness coating film such as a glassy hard coat can be easily peeled off from the coated object. As the alkaline stripping agent (B), for example, a solution in which an alkaline substance is dissolved in a solvent can be mentioned. In particular, a strongly alkaline stripping agent is preferable. Here, the term "strongly alkaline" means that the pH is 12 or more. The pH can be measured by a pH meter according to JIS Z 8802:2011. Examples of alkaline substances include inorganic compounds such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, borax, and sodium silicate; alkanolamine compounds such as monoethanolamine, monoisopropanolamine, diethanolamine, and triethanolamine, and combinations thereof.
[0046] Examples of the solvent include water and hydroxyl-containing organic solvents, such as alcohol-based solvents and glycol-based solvents. Examples of alcohol-based solvents include methyl alcohol, ethyl alcohol, propyl alcohol, butyl alcohol, benzyl alcohol, 2-methylbenzyl alcohol, 3-methylbenzyl alcohol, 4-methylbenzyl alcohol, α-methylbenzyl alcohol, phenethyl alcohol, and combinations thereof. Examples of glycol-based solvents include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monoamyl ether, ethylene glycol monohexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol monophenyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropylene ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tripropylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, and the like; and combinations thereof.
[0047] The alkaline stripping agent (B) can be applied by known methods such as mop coating, spray coating, roller coating, brush coating, and flow coating, and can be appropriately selected according to the conditions of the removal work site. After application, the alkaline stripping agent (B) is cured to penetrate the glassy hard coat. The curing time is, for example, 1 to 48 hours, preferably 3 to 24 hours. The ambient temperature during curing may be room temperature, but may be heated as necessary. In order to prevent the alkaline stripping agent (B) from drying and increase its permeability, it is preferable to add a step of covering the surface protective coating film with a sheet material after application of the alkaline stripping agent (B) and before the step (III) described below.
[0048] Process (III): The alkali-treated vitreous hard coat is then ground using an abrasive (C) containing abrasive grains. The surface protective coating formed on the object is scraped off and removed by the grinding process using abrasives (C). The grinding process is carried out by wiping off the alkaline stripping agent (B) as necessary, spraying water, and pressing and rubbing the abrasives (C) against the surface.
[0049] Specific examples of the abrasive (C) are the same as those exemplified for the abrasive (A). The grain size of the abrasive (C) is preferably finer than that of the abrasive (A), for example, grain size #40 to 1000. By having the grain size within this range, damage to the coated object is suppressed, and even a surface protective coating film formed on an uneven coated object can be easily removed. A diamond pad with a grain size of #40 to 1000 is a preferred example of the abrasive (C).
[0050] The grinding operation may be performed manually or automatically by machine, and can be carried out in the same manner as in step (I). From the viewpoint of suppressing damage to the coated object and removability of the surface protective coating formed on the coated object having an uneven shape, a polishing device that performs a rotational motion in a horizontal direction relative to the surface protective coating is also preferred in step (III), and furthermore, it is more preferred from the viewpoint of exerting coating removal performance that the abrasive (C) is disk-shaped and is attached to a rotary electric polisher. Specific examples of the polishing device are the same as those exemplified in step (I).
[0051] In this way, the surface protective coating is peeled off and removed from the substrate. In the method of the present invention, the grinding trace creating step (I) and the alkaline stripping agent (B) penetration step (II) are carried out in combination, so that a high-hardness surface protective coating that is firmly attached to the substrate can be easily removed without damaging the substrate. EXAMPLES
[0052] The present invention will now be described in more detail with reference to the following examples, but the present invention is not limited to these examples. In the following examples, "parts" and "%" refer to "parts by mass" and "% by mass", respectively.
[0053] [Preparation of coating agent for forming primer coat for peel test] A base agent was produced by mixing 200 parts (100 parts solids) of a water dispersion of hydroxyl-containing acrylic resin (Note 1), 100 parts of deionized water, 30 parts of dipropylene glycol dimethyl ether, and 1.4 parts (0.7 parts solids) of "Surflon S-211" (product name, manufactured by AGC Seimi Chemical Co., Ltd., perfluoroalkyl carboxylic acid surfactant, 50% solids), and stirring for 15 minutes with a disper. Next, 75 parts (60 parts solids) of a polyisocyanate compound (Note 2) and 0.3 parts of dioctyltin dilaurate were added as curing agents, and mixed with a disper to produce a coating for forming a primer coat. The Martens hardness of the coating film produced by the coating agent was 52 N / mm 2 It was.
[0054] (Note 1) Water dispersion of hydroxyl-containing acrylic resin: In a 2-liter glass 4-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet, 400 parts of deionized water and 1 part of sodium dodecylbenzenesulfonate were charged, and the air inside was replaced with nitrogen, and the temperature was raised to 82°C while stirring. In a separate container, 440 parts of deionized water, 40 parts of sodium dodecylbenzenesulfonate, and 2 parts of ammonium persulfate were added, and after thorough stirring, a mixture consisting of the following monomer composition was added thereto to form an emulsion, and the emulsion was dropped at a constant rate over 4 hours into a glass 4-neck flask kept at 82°C. After the dropwise addition, the mixture was further stirred at 82°C for 2 hours, cooled to 40°C, and the pH was adjusted to 7.5 with ammonia water to obtain an aqueous dispersion of a hydroxyl-containing acrylic resin with an average particle size of 150 nm and a resin solid content of 50%. Styrene 100 parts Methyl methacrylate 310 parts n-Butyl acrylate 182 parts 2-Hydroxyethyl acrylate 192 parts Acrylic acid 16 parts.
[0055] (Note 2) Polyisocyanate compounds: The following mixture was placed in a 2-liter glass four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet, and stirred at 80°C for 5 hours under a nitrogen atmosphere to obtain a sulfonic acid-modified polyisocyanate compound with a solid content of 80% and an isocyanate group content of 16.0%. Hexamethylene diisocyanate nurate 970 parts 3-(Cyclohexylamino)propanesulfonic acid 30 parts Dimethylcyclohexylamine 17.4 parts 1-Methoxypropyl-2-acetate 254 parts.
[0056] [Preparation of coating agent for forming a glassy hard coat for peeling test] A coating agent for forming a hard coat layer was obtained by stirring 62.5 parts of epoxy silane oligomer (Note 3) (50 parts as solids), 125 parts of Snowtex O-40 (trade name, Nissan Chemical Industries, Ltd., water-dispersed acidic colloidal silica with an average particle size of 23 nm, pH=3, solids content 40% by mass) (50 parts as solids), 15 parts of 3-glycidoxypropyltrimethoxysilane (15 parts as solids), 10 parts of methyltrimethoxysilane, 2 parts of phosphoric acid as a curing catalyst, and 40 parts of 3-methoxy-3-methyl-1-butanol as a dilution solvent until homogenous using a disperser. The Martens hardness of the coating film produced by the coating agent was 180 N / mm 2 It was.
[0057] (Note 3) Epoxy silane oligomer: 236 parts of 3-glycidoxypropyltrimethoxysilane and 32 parts of methanol were placed in a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen inlet tube, and mixed and stirred at room temperature. Next, 10 parts of 0.05N hydrochloric acid were added dropwise over 30 minutes while stirring, and the mixture was stirred for another 30 minutes. The mixture was then heated to 75°C using a mantle heater, and refluxed for 2 hours while simultaneously removing the by-product methanol. After cooling to room temperature, the mixture was filtered to obtain an epoxy silane oligomer with a solid content of 80%. The epoxy silane oligomer had a weight average molecular weight of 1,100 and an epoxy equivalent of 220 g / eq.
[0058] [Preparation of test bed for peeling test] A long PVC sheet (commercial product, thickness 2 mm) with a wood grain pattern and fine grooves (depth about 1 mm) was prepared as a flexible substrate with a fine concave surface. A primer coat forming coating agent was applied to the surface of a floor measuring 740 x 680 cm with this substrate attached, using a mop, and dried for 16 hours under conditions of 23°C temperature and 50% RH humidity to form a primer coat layer with a dry thickness of 10 μm. A glassy hard coat forming coating agent was applied on top of this using a mop, and dried for 4 days under conditions of 23°C temperature and 50% RH humidity to form a top coat with a dry thickness of 11 μm, and a peel test bed with a protective coating film of a urethane coating film as the lower primer coat and a glassy hard coat as the top coat was prepared. Next, in order to perform peel tests under different conditions, the test substrate was divided into sections according to the number of tests to be performed.
[0059] [Peel test] The peeling tests for peeling the surface protective coating were carried out under various conditions, and the peeling state of the protective coating and the state of the coated object after the test were evaluated. Ranks S, A, and B were judged as passing, while ranks C, D, and E were judged as failing.
[0060] Example 1 After attaching a disk-shaped diamond pad with a grain size of #80 (manufactured by Resibon Japan, product name "Alta Floor Pad #80") to an electric floor polisher weighing 39 kg, the rotation speed of the electric floor polisher (a polishing device that rotates horizontally relative to the surface protective coating surface) was set to 240 rpm, and while applying the weight of the polisher, the diamond pad surface was pressed against the top coat of the test substrate surface at a rotation speed of 240 rpm, and one section of the test substrate was polished with the diamond pad while spraying water all over, generating scratches on the entire glassy hard coat. After that, a liquid commercially available alkaline stripper (sodium hydroxide, potassium hydroxide, alkanolamine, glycol-based solvent, water-containing, pH 13 or higher) was applied to the entire glassy hard coat with the scratches using a mop, and the top coat was left at room temperature for 2 hours. When the top coat was touched by hand after leaving it, it was confirmed that it had softened. After that, the pad attached to the electric polisher was replaced with a disk-shaped diamond pad with a grain size of #400 (Apico's product name "Twister Pad Red"), and the polisher was pressed against the softened topcoat surface while rotating at a speed of 240 rpm, and polishing was performed while the release agent remained. At the points where the diamond pad hit, the topcoat and primer coat turned into scraps (small lumps) like eraser shavings and fell off in pieces. This polishing work was continued until the coated object (PVC sheet) was exposed.
[0061] Example 2 A peel test was carried out in the same manner as in Example 1, except that after application of the release agent, wrapping with a vinyl sheet was performed and the penetration time was changed to 3 hours.
[0062] Examples 3 to 7 A peeling test was carried out in the same manner as in Example 2, except that the grit size of the diamond pad used for polishing performed before and after application of the stripping agent and the stripping agent penetration time were set to the conditions shown in Table 1.
[0063] Comparative Example 1 After attaching a disk-shaped diamond pad with a grain size of #80 (trade name: "Alta Floor Pad #80" manufactured by Nippon Resibon Co., Ltd.) to an electric polisher weighing 39 kg, the rotation speed of the electric polisher (a polishing device that rotates horizontally relative to the surface protective coating surface) similar to that of Example 1 was set to 240 rpm, and the diamond pad surface was pressed against the top coat on the surface of the test coating at a rotation speed of 240 rpm while applying the weight of the polisher, and the top coat and primer coat of one section of the test coating were scraped off. This work was carried out until only a small amount of the primer coat of the lower layer remained. After that, the primer coat was carefully scraped off the coating film partially remaining on the coating object using a disc sander equipped with one disk-shaped diamond pad of #200, while being careful not to scratch the coating object.
[0064] Comparative Example 2 A peeling test was carried out in the same manner as in Comparative Example 1, except that the grit size of the diamond pad attached to the disk sander was #400.
[0065] Comparative Example 3 A stripping test was carried out in the same manner as in Example 3, except that a liquid, commercially available neutral stripping agent (containing water, benzyl alcohol, and heavy aromatic petroleum solvent naphtha) was used instead of the alkaline stripping agent in Example 3. The topcoat was softened when touched by hand after penetration of the stripping agent.
[0066] Comparative Example 4 A peeling test was carried out in the same manner as in Example 3, except that polishing before application of the release agent was not carried out. The peel test conditions and evaluation results are shown in the table below.
[0067] [Table 1]
[0068] (*) Peeling condition of protective coating S: No protective coating remaining at all on either the grooves or flat surfaces. A: Less than 1% of the protective coating remains only in the grooves, but there is no protective coating remaining on the flat surfaces. B: 1% to less than 5% of the protective coating remains in the grooves and less than 1% on the flat surfaces, but it is not noticeable. C: 5% to less than 10% of the protective coating remains in the grooves, and 1% to less than 5% of the protective coating remains on the flat surfaces, and is noticeable. D: 10% to less than 15% of the protective coating remains in the grooves, and 5% to less than 10% of the protective coating remains on the flat surfaces, which is quite noticeable. E: More than 15% of the protective coating remains in the grooves and more than 10% remains on the flat surfaces, which is quite noticeable.
[0069] (*) Condition of the substrate after peeling S: No scratches or dullness was observed on the coated object. A: No scratches are found on the coated object, but slight gloss loss is found. B: Less than 1% of the coated object has scratches, but they are not noticeable. C: Scratches are noticeable on the coated object, 1% or more but less than 5%. D: Scratches are found on 5% to less than 10% of the coated object and are quite noticeable. E: Scratches are found on 10% or more of the coated object and are quite noticeable.
[0070] [Consideration] As can be seen from the results shown in Table 1, it was confirmed that even a hard surface protective coating film with strong bonds such as a glassy hard coat can be sufficiently removed by grinding the surface with an abrasive (A) containing abrasive grains, applying and penetrating an alkaline stripping agent (B), and then grinding the surface again with an abrasive (C) containing abrasive grains. Furthermore, it was confirmed that even a surface protective coating film that has penetrated into complicated areas can be sufficiently removed. (Examples 1 to 7) On the other hand, in Comparative Example 1, where there was no process of penetrating with the alkaline stripping agent (B) and only physical stripping was performed, the surface protective coating in intricate areas could not be completely removed, resulting in damage to the substrate. In Comparative Example 2, the grain size of the abrasive was adjusted, but although scratches on the substrate could be suppressed, some of the protective coating remained on the flat surfaces and in the grooves. Furthermore, when a neutral stripping agent was used as the penetrating stripping agent, although the coating film was softened, the surface protective coating film on the flat surfaces and intricate areas could not be completely removed (Comparative Example 3).Furthermore, when the step of grinding the surface with an abrasive (A) was not carried out in advance, the surface protective coating film remained conspicuously on the flat surfaces even when the alkaline stripping agent (B) was sufficiently penetrated, and the stripping removability was insufficient (Comparative Example 4).
Claims
1. A substrate having a surface protective coating film with a glassy hard coat as a top coat is provided with A step (I) of grinding the vitreous hard coat using an abrasive (A) containing abrasive grains; A step (II) of applying an alkaline stripping agent (B) to the vitreous hard coat having the grinding marks formed in the step (I) to allow the stripping agent (B) to penetrate into the vitreous hard coat; A step (III) of grinding the vitreous hard coat treated with alkali in the step (II) using an abrasive (C) containing abrasive grains to remove the surface protective coating film and expose the substrate; A method for removing a surface protective coating film from an object to be coated.
2. The method according to claim 1 , wherein the surface of the substrate is flat or has an uneven surface.
3. The removal method according to claim 1 , wherein the glassy hard coat contains, as a main component, a silica skeleton derived from three-dimensional siloxane bonds.
4. 2. The method according to claim 1, wherein the glassy hard coat is formed by applying a coating agent containing a hydrolyzable silane and / or a condensate thereof and colloidal silica.
5. 2. The method according to claim 1, wherein the surface protective coating is a multi-layer coating in which the top coat is the vitreous hard coat and the primer coat is a polyurethane coating.
6. 2. The method according to claim 1, wherein the abrasive (A) is a diamond pad having a grain size of #40 to #240.
7. 2. The method according to claim 1, wherein the abrasive (A) is disk-shaped and attached to a rotary electric polisher.
8. The removal method according to claim 1 , further comprising the step of covering the surface protective coating with a sheet material after step (II) and before step (III).
9. 2. The method according to claim 1, wherein the abrasive (C) is a diamond pad having a grain size of #40 to #1000.
10. 2. The method according to claim 1, wherein the abrasive (C) is disk-shaped and attached to a rotary electric polisher.
Citation Information
Patent Citations
Active energy ray-curable resin composition for floor material, coated floor material, method for producing coated floor material and floor material contamination prevention method
JP2018141104A
Peeling material of hard coating film and peeling method
JP2023020782A
Coating composition and method for forming surface protection film
WO2018151271A1